Appropriative Painting on Illustrated Surfaces as Alternative Art Media - Rahim, Muhamad Ali (Institut Seni Indonesia Yogyakarta, 2025)
In the evolution of contemporary art, drawings and/or paintings remains a resilient medium yet continues to exhibit increasingly diverse visual expressions. Postmodern paintings frequently explore styles through eclectic elements and still predominantly utilize traditional techniques involving colored paint on flat surfaces as an artistic powerful paradigmatic medium. The author was interested to investigate and study further in research, as well as to innovate practically by utilizing the concept of appropriation as a stylization pattern to create images over existing images (overlay drawings). This approach consisted of several methods used include the stages of exploration, improvisation, and implementation; starting with visual comparison, experimentation with drawing media, and the application of the eclecticism of the painting by utilizing a plane material with a cross-section of the image/pattern as a medium of two-dimensional artwork (painting). As contemporary works of art often seeks to present uniqueness that triggers reflection, this research-creation aims to explore and expand the possibilities of using different— if not new—painting media while still maintaining the dimensional aspects of its flat surface. The findings of this research are an alternative offer to trigger innovation in different works of art, presenting a shift in conventional views that stimulate discussion of the novelty of fine art, while also being useful in providing an overview of the essence of postmodernism that reflects the complexity of contemporary art through elaboration of conventional painting ‘standards’. Ultimately, this creation yields a distinctive alternative painting work due to its eclectic visual mix. The implication is the expanding possibilities of using media and creative patterns in creating a painting, which is not merely limited to a plain surface, but alternatively responds to the surface of a pictorial medium by adding images to it using conventional painting techniques.